To the question of the expediency of the official recognition of the term «anthropocene» (on the example of the regions of Eurasia) - N. A. Bogdanov (Известия высших учебных заведений: Геология и разведка, 2019)
The transformation of the environment (EM), its geological components, due to the intensification of technogenesis caused a response in foreign science: it was proposed to name the period of the development of this process as «anthropocene» and officially recognize the term as a subsection of the Holocene era in the framework of the Quarter General Stratigraphic scale (Anthropogen). This recognition implies a planetary representativeness of the process, which is actually absent. There is also no consensus on the time threshold for the start of the estimated period. Various authors date the threshold from 8 thousand years ago (comparable in duration with the Holocene) to the present time. Illustrative examples of the anthropogenic transformations of the EM are presented in Eurasia. Thus, in Western Europe, the intensification of such activities is associated with the beginning of the industrial revolution (the end of the 18th century), which was observed in Russia about 100 years later (the second half of the 19th century). In the South-Eastern Baltic, conflicting changes in the state of the water area, shores and the bottom have been occurring since the end of the 19th century and up to the present. They are mechanical (catastrophic abrasion of the coast, port of Libava), ecological and radiation-hygienic in nature (pollution of the water area, burial at the bottom of the chemical waste of World Wars, emissions of deadly shells and bombs, echoes of the Chernobyl disaster). The reference point for the use and testing of nuclear weapons since 1945 is the fallout of radionuclides in Eurasia. Temporary thresholds and powers of influence are determined by the industrial development of civilizations, which is uneven in time and space. In remote corners of the planet, the term «anthropocene» loses its meaning. An analysis has shown that the term’s ratification within the chronostratigraphic scale is unacceptable.